2019
DOI: 10.1111/resp.13714
|View full text |Cite
|
Sign up to set email alerts
|

miRNA sequencing reveals miRNA‐4508 from peripheral blood lymphocytes as potential diagnostic biomarker for silica‐related pulmonary fibrosis: A multistage study

Abstract: Background and objective: This study aimed to identify miRNA as potential diagnostic biomarkers for silicarelated pulmonary fibrosis (SPF). Methods: We first performed a comprehensive miRNAseq screening in PBL of eight subjects exposed to silica dust (four individuals with SPF and four healthy controls). The promising miRNA were then evaluated in the first-stage validation using an independent GEO data set (GSE80555) of 6 subjects (3 individuals with SPF and 3 healthy controls), followed by a second-stage vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Although surgery and some replacement therapies including immunotherapy have been widely applied for pRCC patients, the limited response rate and unsatisfied outcomes motivated us to further explore the more appropriate methods to improve the therapeutic With the more distinct advantages of the relatively stable state in tissues and the prominent testability, miR-NAs become increasingly promising to be indicators to forecast prognosis [29,30]. Gluud et al demonstrated the indicating roles of miR-223, miR-191 and miR-342 on therapeutic outcomes of cutaneous T cell lymphomas [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although surgery and some replacement therapies including immunotherapy have been widely applied for pRCC patients, the limited response rate and unsatisfied outcomes motivated us to further explore the more appropriate methods to improve the therapeutic With the more distinct advantages of the relatively stable state in tissues and the prominent testability, miR-NAs become increasingly promising to be indicators to forecast prognosis [29,30]. Gluud et al demonstrated the indicating roles of miR-223, miR-191 and miR-342 on therapeutic outcomes of cutaneous T cell lymphomas [31].…”
Section: Discussionmentioning
confidence: 99%
“…With the more distinct advantages of the relatively stable state in tissues and the prominent testability, miRNAs become increasingly promising to be indicators to forecast prognosis [ 29 , 30 ]. Gluud et al demonstrated the indicating roles of miR-223, miR-191 and miR-342 on therapeutic outcomes of cutaneous T cell lymphomas [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 For example, the expression level of miR-4508 from peripheral blood lymphocytes was lower in subjects with silica-related pulmonary fibrosis than that in healthy controls. 9 Elevated expression of miR-7 relieved silica-induced pulmonary fibrosis by blocking epithelial-mesenchymal transition progress. 10 Our previous study also indicated that miR-1224-5p targeted BECN1 to regulate mitochondrial damage in silica-induced pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of miRNAs and the disorder of intracellular signal cascade are closely correlated with the pathological process of pulmonary fibrosis 8 . For example, the expression level of miR‐4508 from peripheral blood lymphocytes was lower in subjects with silica‐related pulmonary fibrosis than that in healthy controls 9 . Elevated expression of miR‐7 relieved silica‐induced pulmonary fibrosis by blocking epithelial‐mesenchymal transition progress 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al . screened workers with silicosis and well‐matched exposed but unaffected controls for differentially expressed micro‐RNA (miRNA) in peripheral blood lymphocytes . miRNA are known to be key regulators of gene transcription which fine tune intracellular mRNA and subsequent protein production.…”
mentioning
confidence: 99%